Application of ultrasound in medicine Part ii: the ultrasonic transducer and its associated electronics - Soler López, Fernando A.; Mayorga Betancour, Manuel A.; Cruz Salazar, Emeterio (TECCIENCIA, 2013)
This paper introduces the reader to a review and analysis of various ultrasound (us) applications in the medical field. First, the transducer is shown, along with a diagram of the basic electronics that it uses to generate and receive signals that allow the reconstruction of images, for medical purposes. Also, us practical uses in medical therapy is shown. This subject is addressed by combining the physical principles involved in the us application, with the implemented technology and the modes of operation for non-invasive studies of pathologies related to brain, heart, and eyes such as injuries, tumors and hematomas. The methodology used in this article also suggests an analysis method for the us scientific and technological research principles combined for their implementation in medical applications.